Scarcity: The true cost fo not having enough - Mullainathan, Sendhil; Shafir, Eldar (London Penguin Book Ltd., 2013)
Why can we never seem to keep on top of our workload, social diary or chores? Why does poverty persist around the world? Why do successful people do things at the last minute in a sudden rush of energy? Here, economist Sendhil Mullainathan and psychologist Eldar Shafir reveal that the hidden side behind all these problems.